PENGARUH PREPARASI UBI JALAR (Ipomoea batatas) SEBAGAI BAHAN PENGENTAL TERHADAP KOMPOSISI KIMIA DAN SIFAT ORGANOLEPTIK SAUS BUAH MERAH (Pandanus conoideusL) - Murtiningrum Murtiningrum; M Meilan Lisangan; Yonince Edoway (Agroindustrial Technology, University of Trunojoyo Madura, 2012)
The aim of this study was to determine the chemical composition and organoleptic properties of red fruit sauce due to the enriched of sweet potato as thickeners agent that was prepared in different forms. The sweet potatoes were prepared in some form, that was sweet potato starch, sweet potato flour, fresh grated sweet potato and sweet potato boiled and CMC was used for as comparison. The selection of the best treatment sauce formulations based on the total carotene content of the sauce. The red fruit sauce enriched sweet potato boiled as thickeners have the highest content of total carotenoids was 5.529 ppm and water content, ash, fat, protein, and carbohydrate were 75.44%, 8.05%, 59.97%, 8.49%, and 23.54%, respectively. The panelists preference scores of color, flavor and textur of the best sauce formulation was 3.63 (neutral), 3.47 (neutral) and 4.17 (like), respectively.